Markups for consumers - Bernhard Ganglmair; Alexander Kann; Ilona Tsanko (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
A central motivating factor for studying price markups is their effect on consumer welfare. Reported estimates of (firm-level) price markups in the literature, however, are often focused on industry or cross-country comparisons. These treat different industries equally rather than based on how relevant they are for consumers. We propose markup measures in which firm-level price markups are weighted according to consumption expenditures in the respective industries. Using a concordance table between consumption categories (otherwise used for the calculation of consumer price indices) and a firm's industry classification, we report results for Germany for the years 2002 through 2016. We find that consumption-weighted price markups are higher than the conventionally reported revenue-weighted markups. We further show that consumption-weighted markups have increased faster, in particular for medium-income households, which highlights a potential role of price markup as a contributing factor to changes of inequality in society.
Keywords: D63; E31; K21; L11; L40; 330; COICOP; consumption weights; Germany; inequality; price markups